Main potential drivers of trout population dynamics in bypassed stream sections. Issue 3 (22nd June 2016) - Tissot, Laurence; Bret, Victor; Capra, Hervé; Baran, Philippe; Gouraud, Véronique
Abstract: The key role of hydrological variability in structuring brown trout populations is well established. However, the influence of additional drivers is more difficult to identify. The implementation of long‐term monitoring and the development of reliable tools can help to reveal fine local drivers structuring fish populations in contrasted flow regimes. This study used data series for nine reaches monitored for nine to nineteen years in four French salmonid streams. Study reaches were within five bypassed sections influenced by instream flow. A deterministic trout population dynamics model was applied on each reach, with calibration and validation procedures. Results revealed that biological drivers structured all reaches similarly. In addition, seven other drivers were identified. Among these additional drivers, hydrology mainly explained temporal fluctuations in trout density, regardless of reach. Three drivers independent of hydrology were also revealed: poor water quality, limited spawning area and the effect of power plant operations (overtopping, flushing or plant shutdown). All drivers influenced the whole bypassed section and were never limited to the scale of the reach (sampling area). Further analyses of each driver are now needed, to regionalise and quantify their respective impact precisely. Thus, assessment of trout population status would be simplified, enabling implementation of efficient management rules.